AquaNet - Bacterial Abundance from Erssjön AquaNet platform - Skogaryd Research Catchment (University of Gothenburg, 2019)
Mesocosm experiment focusing on fish pulse and light reduction as treatment effects ran simultaneously at the SITES stations Asa, Erken, Skogaryd, Svartberget and Bolmen during summer 2017. Data contains number of bacterial cells per volume unit (million cells L-1).
Skogaryd Research Catchment (2019). AquaNet - Bacterial Abundance from Erssjön AquaNet platform, 2017-06-20–2017-09-25 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/-kG9VYPINemyX1U0KD3FL_uu
Keywords: SITES AquaNet; Bacteria/Archaea; Biomass Dynamics; Ecosystem functions; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap